A Robust Oxygen Microbubble Radiosensitizer for Iodine‐125 Brachytherapy. Issue 7 (10th February 2021) - Peng, Sheng; Song, Ruyuan; Lin, Qingguang; Zhang, Yanling; Yang, Yuanzhong; Luo, Ma; Zhong, Zhihui; Xu, Xiaonan; Lu, Ligong; Yao, Shuhuai; Zhang, Fujun
Abstract: Iodine‐125 ( 125 I) brachytherapy, a promising form of radiotherapy, is increasingly applied in the clinical treatment of a wide range of solid tumors. However, the extremely hypoxic microenvironment in solid tumors can cause hypoxia‐induced radioresistance to 125 I brachytherapy, resulting in therapeutic inefficacy. In this study, the aim is to sensitize hypoxic areas in solid tumors using ultrasound‐activated oxygen microbubbles for 125 I brachytherapy. A modified emulsion freeze‐drying method is developed to prepare microbubbles that can be lyophilized for storage and easily reconstituted in situ before administration. The filling gas of the microbubbles is modified by the addition of sulfur hexafluoride to oxygen such that the obtained O2 /SF6 microbubbles (OS MBs) achieve a much longer half‐life (>3×) than that of oxygen microbubbles. The OS MBs are tested in nasopharyngeal carcinoma (CNE2) tumor‐bearing mice and oxygen delivery by the OS MBs induced by ultrasound irradiation relieve hypoxia instantly. The post‐treatment results of brachytherapy combined with the ultrasound‐triggered OS MBs show a greatly improved therapeutic efficacy compared with brachytherapy alone, illustrating ultrasound‐mediated oxygen delivery with the developed OS MBs as a promising strategy to improve the therapeutic outcome of 125 I brachytherapy in hypoxic tumors. Abstract : Tumor‐specific ultrasound‐activated oxygen microbubbles are developed to sensitize hypoxic tumor cells for 125 I brachytherapy. The microbubbles, lyophilized for storage and easily reconstituted in situ before administration, have much better stability by the addition of sulfur hexafluoride into oxygen. Ultrasound‐mediated oxygen delivery with the microbubbles demonstrate a greatly improved therapeutic outcome of 125 I brachytherapy in hypoxic tumors.